Spectrum and review of MRI findings in hypophysitis - Kadiyala, Niharika; Murali, Arunan; Sai, Venkata (International Journal of Research in Medical Sciences, 2018)
Inflammation of the pituitary infundibulum and pituitary gland (hypophysis) is called hypophysitis. The causes may be primary (lymphocytic hypophysitis, granulomatous hypophysitis, xanthomatous hypophysitis, necrotizing hypophysitis) or secondary due to spread of disease from elsewhere in the body. Authors report three cases of primary hypophysitis with radiological findings ranging from simple thickening of the infundibulum, posterior pituitary (infundibuloneurohypophysitis), thickening of the entire gland and infundibulum (panhypophysitis) and mass forming lesion in the anterior pituitary gland (adenohypophysitis). Diagnosis is arrived based on combined findings of clinical features, endocrinological assessment, Immunological markers, imaging studies and histopathology (if necessary). Conservative, supportive treatment is usually the treatment of choice with surgical decompression reserved for cases with extensive mass effect. Authors conclude that hypophysitis should be considered as a differential diagnosis for lesions of the pituitary.